ANALISIS KUALITAS SALA UDANG REBON - Ramadhani, Sri Retno; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2016)
Improved quality of sala lauak that can be done is by varying flavors, one of which uses rebon. This study aimed to analyze the effect of using rebon as much as 0 g, 40 g, 60 g, 80 g and 100 g of the quality of shape, color, aroma, texture and flavor to the sala rebon generated. This study belongs to the kind of pure experiment (true experiment) with a completely randomized design method. The research was carried out in the workshop Catering Department of IKK, FPP, UNP. The data used is primary data which can be directly from the 30 panelists by filling out a questionnaire. The data has been obtained and tabulated in tables and do Variant Analysis (ANOVA), if different from the real continued with Duncan test. Results of data analysis obtained the highest score overall achievement is the quality of shape (rounded) 4.29 (X0), the quality of the form (uniform) 4.08 (X1), color quality (tawny) 4.00 (X4), the quality of the scent ( rebon) 4.20 (X4), the quality of the texture (hollow) 4.11 (X0), the quality of taste (savory) 4.20 (X4) and the taste quality (rebon) 4.67 (X4).